Homochiral porous coordination polymers with a rare utk topology and two types of uniform channels for enantioseparation. Issue 20 (27th April 2017) - Zou, Changchang; Li, Qianqian; Cheng, Fujun; Wang, Haijun; Duan, Jingui; Jin, Wanqin
Abstract : A pair of enantiopure, chiral, porous, coordination polymers with rareutk topology and two types of helical chains were designed and prepared, exhibiting promising enantioseparation towards racemic 1-phenyl-1-propanol. Abstract : A pair of enantiopure chiral porous coordination polymers (PCPs) with a rareutk topology were prepared using derivatives ofl -/d -alanine and Zn(CH3 COO)2 ·2H2 O. The framework integrated two types of parallel and uniform 1D channels that were constructed by self-stranding of three equal helical chains and a single helical chain. Among them, the right-handed PCPd -NTU-18 showed enhanced enantioseparation towards racemic 1-phenyl-1-propanol.